(untitled) (International Journal of Engineering and Computer Science, 2013)
- In mobile ad-hoc network (MANET), a node may drain its power or diverge without giving any notice to its neighboring nodes. It causes changes in network topology, and thus, it significantly degrades the performance of a routing protocol. Several routing protocol studies are based on node lifetime and link lifetime. The main objective here is to evaluate the node lifetime and the link lifetime utilizing the dynamic nature, such as the energy drain rate and the qualified mobility estimation rate of nodes. These two performance metrics are incorporated by Route lifetime-prediction algorithm. The exponentially weighted moving average method is used to estimate the energy drain rate. The receiver can measure the signal strength when it receives the packets from sender in same power level and then it calculates the distance between two nodes by applying the radio propagation model. The proposed EDNR protocol outperforms the conventional DSR protocols and it is simulated using NS2.